Assessment of herbal products derived from certain Egyptian plants used for amelioration of lipid disorders - Nessma Elsayed Mohamed Ali; Hesham I. Elaskary; Soheir M. Elzalabani (Cairo : Nessma Elsayed Mohamed Ali, 2018)
Introduction: Lipid disorders are manifested mainly as hyperlipidemia. Development of efficient and economic anti-hyperlipidemicdrug, guided by WHO requirements, is of national economic significance. Three Egyptian drugs: artichoke leaves, carob pods and barley beta-glucan were selected based on reported data and their efficiency in management of lipid disordersassessed. Experimental The identity and quality of the selected drugs were confirmed through proximate analysis, nutritional evaluation, macro- and microscopical examination. Appropriate extraction procedures were designed to prepare specified aqueous extractsofartichoke (A-Aq) and carob (C-Aq). Barley beta-glucan was purchased from official supplier. The hypolipidemic efficiency of the tested samplesand their combination (200 mg/kg b.w., each) was investigated incholesterol-fed male albino rats, by measuring some biochemical parameters(triglycerides (TGs), total cholesterol (TC), LDL,HDL, risk ratio and risk factor).Several trials were adopted to develop HPLC analysis. HPLC standardization of the bioactive mixture was carried out using quercetin as reference standard
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Pharmacognosy
Issued also as CD
Keywords: Artichoke; Carob; Lipid disorders